Attitudes towards parental employment across Europe, in Australia and in Japan - Isabella Buber-Ennser; Ralina Panova (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2014)
Based on the Generations and Gender Survey this paper studies attitudes towards parental employment in 14 European countries - among them ten located in central and eastern Europe, Australia and Japan. In a multivariate framework we examine how the acceptance of the employment of mothers of pre-school children differs. Our aim is to find out how attitudes vary across countries and sex. Since the role of fathers in the process of socialisation of their children has been underestimated and underinvestigated for a long time, we take the challenge of studying attitude towards fathers' concentration on work. The country-specific ranking in terms of traditional attitudes towards employment of mothers with pre-school children is in tune with the expectations derived from the Second Demographic Transition (SDT) theory, with the exception of Romania. Australia holds a medium position, Japan an ambivalent one. We find a large diversity in the level of traditionalism among the central and eastern European countries. Variation in gender differences is substantial; differences are largest where SDT is at an advanced level. Regarding fathers' concentration on work, the majority presumes negative consequences for children, but the answering pattern shows no clear relation with advancement in the SDT.
Keywords: 300; attitudes; maternal employment; paternal employment; pre-school children; GGS; Second Demographic Transition